Epithelioid sarcoma in children, adolescents, and young adults: Localized, primary metastatic and relapsed disease. Treatment results of five Cooperative Weichteilsarkom Studiengruppe (CWS) trials and one registry. Issue 9 (19th June 2019) - Sparber‐Sauer, Monika; Koscielniak, Ewa; Vokuhl, Christian; Seitz, Guido; Hallmen, Erika; von Kalle, Thekla; Scheer, Monika; Münter, Marc; Bielack, Stefan S.; Ladenstein, Ruth; Fuchs, Joerg; Klingebiel, Thomas; et al.
Abstract: Background: Epithelioid sarcoma (ES) is a rare malignant soft‐tissue tumor. Little is known about the optimal treatment of primary localized (LD), metastatic (MD), and relapsed disease (RD). Methods: Characteristics, treatment, and outcome of 67 patients registered within the Cooperative Weichteilsarkom Studiengruppe CWS‐81, ‐86, ‐91, ‐96, ‐2002P trials and the registry SoTiSaR were analyzed (1981–2016). Results: The median age was 14 years (range, 0.7–26.9); 53 patients had localized disease (LD) and 14 metastatic disease (MD). A total of 58 of 67 patients were treated with primary resection. Resection was microscopically complete (R0) in 35, microscopically incomplete (R1) in 12, macroscopically incomplete (R2) in 20 patients. Radiotherapy (RT) was administered to 33 of 67 patients and 49 of 67 patients received chemotherapy (CHT). Complete remission (CR) was achieved in 45 of 53 (85%) patients with LD. Twenty‐seven of 53 patients relapsed after a median time of 0.9 years (range, 0.1–2.3). Relapse therapy consisted of resection ( n  = 19/27), RT ( n  = 10/27), CHT ( n  = 12/27), and limb perfusion ( n  = 3/27). The five‐year event‐free survival and overall survival of patients with LD, MD, and RD was 35% (± 12, CI 95%) and 58% (± 14, CI 95%), 7% (± 14, CI 95%), and 9% (± 16, CI 95%), 24% (± 17, CI 95%), and 40% (± 20, CI 95%), respectively. Tumor size, IRS group, tumor invasiveness, nodal status, and best resection correlated with a favorable prognosis in patients with LD while best resection was the only significant factor in patients with RD. Conclusions: Complete tumor resection correlates with long‐term survival in patients with ES.